Effects of Flavonoid Fraction of Echinops Mosulensis on Induced Parkinson’s Disease Model in Mice - Asmaa Abdulwahab Ahmed; Haitham Mahmood Kadhim (Iraqi Journal of Pharmaceutical Sciences, 2025)
Toxins, especially 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), are among the most commonly utilized models of Parkinson’s disease (PD) based on the method utilized, MPTP causes different changes like striatal dopamine depletion , and behavioral abnormality. Phytochemical analysis of Echinops mosulensis extract indicated that there was significant amount of flavonoid present in extract. Flavonoids are belonging to several kinds of plant polyphenols exert a potent antioxidant, neuroprotective, and anti-inflammatory properties. The aim of present study was to investigate neuroprotective effect of flavonoid fractions of Iraqi Echinops mosulensis on induced PD model in mice. Forty male mice were randomly arrayed in 4 groups (10 mice in each group). Group 1: healthy normal control group received distilled water orally via gavage tube for 25 days. Group 2: induction group received MPTP (30mg/kg/day) intraperitoneally for 5 consecutive days to achieved model of PD then continue with distilled water orally via gavage tube for 25 days. Group 3: the positive control group administered pramipexole orally (1mg/ kg/ day) for 25 days then the induction was done with MPTP (30mg/kg/day) intraperitoneally 1 hour post-pramipexole from day 15 to 19. Group 4: received flavonoid fraction orally (250 mg/kg/day) for 25 days then the induction was done with MPTP (30mg/kg/ day) intraperitoneally 1 hour post- flavonoid fraction form the day 15 to day 19. At the day 26, the behavior test was done and at the day 27 all animals were sacrificed. Homogenized brain tissue was prepared for analysis. In present study there was significant decreased in Malondialdehyde, interleukin -1beta, cytochrome C, α-synuclein levels of flavonoid fraction accompanied with significant increase in tyrosine hydroxylase level of flavonoid fraction as compared to induction (p≤0.05), as well as significant increase in distance traveled in treated group as compared to induction (p≤0.05) .Additionally, good improvement in histopathological analysis of treated group as compared to induction. In conclusion, flavonoid fraction of E. mosulensis has a neuroprotective effect on MPTP induced PD Model in Mice.